The Clinical Significance of Mesenteric Lymphocytes in Human Colorectal Cancer - Wu, Zi-Xin; Wang, Fei; Li, Liang; Yao, Yuan; Long, Jie; Luo, Qing-Qing; Zhao, Zhi-Bin; Li, Wang-Lin; Cao, Jie; Lian, Zhe-Xiong (Frontiers in Oncology, 2021)
Objective: The mesentery is a potential site of residual tumor in patients with colorectal cancer (CRC). However, the mesenteric immune microenvironment remains unclear. In this study, we investigated the immune landscape of the mesentery, particularly the role of lymphocytes and its association with the clinicopathological characteristics of CRC. Methods: Flow cytometry was used to detect lymphocytes in the paired mesenteric tissue specimens adjacent to the colorectal tumors and normal mesenteric tissue specimens 10 cm away from the colorectal tumor edge and preoperative peripheral blood samples obtained from patients with CRC who underwent surgery. T-distributed stochastic neighbor embedding was utilized to analyze multiparameter flow cytometry data. Multiplex immunohistochemistry was performed to evaluate T cells subsets in the paired mesentery adjacent to the colorectal tumors and normal mesentery. The Fisher’s exact test and non-parametric Wilcoxon’s matched-pairs tests were used for statistical analysis. The non-parametric Mann-Whitney U test was used to determine associations between percentage data and clinical parameters of patients with CRC. Results: We found that immune cells in the normal mesentery were mainly of lymphoid lineage. Compared with peripheral blood, the normal mesentery showed decreased NK cells and the CD4/CD8 ratio and increased CD3+ CD56+, memory CD4+ T, memory CD8+ T, CD4+ tissue-resident memory T (TRM), and CD8+ TRM cells. Compared with the normal mesentery, the mesentery adjacent to the colorectal tumor showed increased B and regulatory T cells and decreased NK, CD3+ CD56+, CD4+ TRM, and CD8+ TRM cells. Moreover, memory CD8+ T cells and plasmablasts are negatively correlated with the depth of invasion of CRC. Increased memory CD4+ T cells are associated with distant metastasis of CRC and high preoperative serum carcinoembryonic antigen levels. Conclusion: The mesentery shows a specific immune microenvironment, which differs from that observed in peripheral blood. CRC can alter the mesenteric immune response to promote tumor progression.